The Addition of Caffeine in EBSS Media by Sperm Swim-up Washing Method Increased the Human Sperm Motility and Acrosomal Reaction - Bagus Komang Satriyasa; J. Alex Pangkahila (Journal of Global Pharma Technology, 2018)
Background: Caffeine, a methylxanthine derivate, had a role as a phosphodiesterase inhibitor, thereby inhibiting the break down of cAMP and increasing its concentration inside the cell. Aim: This study aimed to assess the effect of caffeine in EBSS and evaluated the increase in motility and the acrosomal reaction of spermatozoa using the swim-up method. Method: This was an experimental study using a pre-post test control group design. This study was carried out at the Sexology and Andrology Clinic, Sanglah Hospital in Denpasar Bali. The samples were sperm specimens of eighteen infertile male or volunteers aged 20-40 years. They were divided into two groups: treatment group (caffeine + EBSS) and control group (EBSS). The data were analyzed statistically by normality test (Kolmogorov – Smirnov Goodness of Fit Test), homogeneity test and paired student’s t test. Result: The caffeine addition in EBSS medium increased the sperm motility significantly from 71.94% to 80.28% (p<0.05) and the acrosomal reaction from 83.33% to 88.89% (p<0.05). Conclusion: The addition of caffeine in EBSS medium increased the motility and the acrosomal reaction of the human sperm.Keywords: Caffeine, EBSS, Sperm motility, Acrosomal reaction, Spermatozoa.